Mediacje rówieśnicze jako forma reakcji na konflikt w środowisku szkolnym - Rajewska de Mezer, Joanna (Studia Edukacyjne, 2021)
Conflict is inseparable from human everyday life. Inscribed in the functioning of an individual who enters various social interactions, its occurrence at some stage of life is inevitable. It is based on the divergent interests of the parties striving to achieve a specific goal. Many conflict situations, destructive in their effects and causing a sense of instability and frustration, appear in the school environment among young people. Peer mediation offers a constructive approach to peer conflict, resolving it through conversation, exchange of thoughts and views by parties representing different positions, in the presence of an impartial and neutral mediator, who is their adequately prepared and trained peer. Peer mediation offers a chance for active participation in the search for a mutually satisfactory solution, teaches responsibility for the decisions taken and creates a sense of agency, which is so important in adulthood.